Acute epiglottic abscess presenting with severe airway obstruction in an adult - John Devasagayam, Jonah Seeni; Roy, Steuphen; Johari, Ahmad Hafizuddin (Elsevier Inc., 2026)
Acute epiglottic abscess is a rare but life-threatening condition that can rapidly progress to severe airway obstruction in adults. We report a case of a 43-year-old man presenting with acute odynophagia and progressive respiratory distress. Despite initial medical therapy, his condition deteriorated, necessitating emergency airway intervention. Failed endotracheal intubation due to distorted supraglottic anatomy led to cricothyroidotomy, followed by definitive tracheostomy. Imaging and intraoperative findings confirmed a multiloculated epiglottic abscess, which was surgically drained. Microbiological culture identified Klebsiella pneumoniae, an uncommon pathogen in this condition. The patient showed good recovery with targeted intravenous antibiotics and was successfully decannulated. This case highlights the importance of early recognition, prompt airway assessment, and multidisciplinary management in adult supraglottic infections. Flexible nasoendoscopy plays a crucial role in risk stratification, while surgical drainage remains essential in abscess cases. Delayed diagnosis may result in catastrophic airway compromise.